Flow Injection Analysis with Turbidity Detection for the Quantitative Determination of Mebeverine Hydrochloride in Pharmaceutical Formulations (Baghdad Science Journal, 2022)
The main objective of this paper is to develop and validate flow injection method, a precise, accurate, simple, economic, low cost and specific turbidimetric method for the quantitative determination of mebeverine hydrochloride (MbH) in pharmaceutical preparations. A homemade NAG Dual & Solo (0-180º) analyser which contains two identical detections units (cell 1 and 2) was applied for turbidity measurements. The developed method was optimized for different chemical and physical parameters such as perception reagent concentrations, aqueous salts solutions, flow rate, the intensity of the sources light, sample volume, mixing coil and purge time. The correlation coefficients (r) of the developed method were 0.9980 and 0.9986 for cell 1 and 2 respectively and showed the linearity of response against concentration over the range of 1.0 to 6.5 and 0.7-6.5mmol/L for cell 1 & 2 respectively. The limit of detections (LOD) for cell 1 and cell 2 were 0.28 and 0.21 mmol/L respectively. The intra-day and inter-day precision for two serial estimations of 3.5 and 5.5 mmol/L of MBH exhibited a relative standard deviation of 0.46%, 0.28%, 0.23%, 0.26% and 0.39%, 0.79%, 0.14%, 0.05% for cell 1 & 2 respectively. The accuracy of the developed method has expressed a recovery percentage (Rec %) and error % which was between 99.22 to 101.13 and 99.39 to 101.17 for cell 1 and cell 2 respectively. The ICH guidelines were followed for method validation. The developed method was successfully applied for the determination of MbH in pure and pharmaceutical preparations and the method can be conveniently used for routine analysis in laboratory as a quality control method since the method permits quantitively determination of 60 samples/h.